Surface Modernities: Open-Air Markets, Containment and Verticality in Two Border Towns of Russia and China - Billé, Franck (Journal of Economic Sociology, 2014)
This article focuses on the contrasting urbanisms that characterize the two cities of Heihe and Blagoveshchensk on the Sino-Russian border. Since 1990, with the bulk of international trade taking place on the Chinese side, Heihe has rapidly developed into a modern town; by contrast, Blagoveshchensk appears sedate and almost stagnant. Another stark contrast between the two cities is in the ways in which ideas of modernity are spatialized through their urban practices, with Blagoveshchensk demonstrating a preference for horizontal functionalism while Heihe largely follows the iconic and vertical model found in the megacities of the Chinese south. Foregrounding this very spatial imbalance, the paper argues that the Russian association between horizontality and modernity unwittingly collapses Heihe’s riverfront skyline into a smooth surface lacking depth, and renders invisible those economic drivers that operate below this surface as well as along a vertical axis. As a result of this, spatiality provides an initial cultural grid through which the development, success and modernity of the Other is assessed. The methodology followed in this article is primarily anthropological. The research was carried out in October and November2011. A dozen semi-structured and open-ended interviews were conducted with informants of diverse ages and social backgrounds, including businessmen and women, academics, young professionals and students. This research was funded through a grant by the Newton Trust (Cambridge, UK).